A 71-year Old Male Patient with 20 Hour Onset of Infarct Stroke that was Performed with Intra-Arterial Thrombolysis, Mechanical Thrombectomy, Balloon Angioplasty, and Carotid Stenting: A Case Report - Kurnianto, Aditya; Andhitara, Yovita; Yudistira; Setiadi, Jeffri; Budiman, Jethro (Medica Hospitalia : Journal of Clinical Medicine, 2023)
Introduction: For above 2 decades, the definitive management for acute ischemic stroke is intravenous or intra-arterial thrombolysis (IAT), using recombinant tissue-type plasminogen activator. Recently mechanical thrombectomy (MT) was developed to overcome the problem that intravenous thrombolysis is only effective in removing large artery occlusions in the range of 10-30%. Early treatment with intra-arterial thrombolysis, permanent stent insertion and clot extraction devices evolved into the stent-retriever device used in most of the important trials and, recently, emerged aspiration tool. This case report presented 71-year-old male patient with infarct stroke who performed with MT. Case presentation: This case report presented 71-year-old male patient with the main complaint of right limbs weakness. A non-contrast head CT scan found infarction in the cortical-subcortical left parietal lobe, posterior pericornu of the right lateral ventricle and right temporal cornu periventricular; lacunar infarction in the right and left paramedian pons; old lacunar infarction in the left and right centrum semiovale, left corona radiata, right internal capsule, right parietal lobe white matter, left lentiform nucleus, left posterior crus of the internal capsule-thalamus, right thalamus, right lateral ventricular pericornu and left paramedian pons. The patient underwent cerebral digital substraction angiography (DSA), as well as IAT, MT, balloon angioplasty, and carotid stenting with good clinical outcome. Conclusion: With the overwhelming positive results of studies evaluating the safety, efficiency, and efficacy of mechanical thrombectomy; the standard of care for the treatment of patients with anterior circulation vessel occlusion is becoming clear.